2016
DOI: 10.1086/687410
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing the “Black Box”

Abstract: Scholars sometimes refer to the civil jury decision-making process as a “black box,” because researchers cannot view juries’ interior workings. However, state institutions structure the environment in which disputes arise and determine the rules courts apply, while environmental factors condition courts’ responses to claims. This article utilizes an original data set of civil jury verdicts in five states to examine the influence of cross-state institutional variation and trial location on courts’ dispute resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Certainly, previous research has found that citizen litigiousness in civil cases is not uniform across U.S. judicial systems. Caseloads vary across states due to a number of factors, including the professionalization of the courts, and characteristics of the states' political, social, and economic environments (Dumas 2016;Yates, Tankersley, and Brace 2010). Similarly, U.S. Supreme Court cases do not emerge randomly from the various lower courts but reflect a range of factors, including the strategic choices made by justices (e.g., R. C. Black and Owens 2009;Epstein and Knight 1998;Perry 1991) andlitigants (e.g., Boyd 2015;Caldeira and Wright 1988), the prestige of particular state court systems, as well as the various political, social, and economic circumstances responsible for the events that generated the original complaint (Boyd 2017;Brunn et al 2000).…”
Section: Geographic Variation and The Legal Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Certainly, previous research has found that citizen litigiousness in civil cases is not uniform across U.S. judicial systems. Caseloads vary across states due to a number of factors, including the professionalization of the courts, and characteristics of the states' political, social, and economic environments (Dumas 2016;Yates, Tankersley, and Brace 2010). Similarly, U.S. Supreme Court cases do not emerge randomly from the various lower courts but reflect a range of factors, including the strategic choices made by justices (e.g., R. C. Black and Owens 2009;Epstein and Knight 1998;Perry 1991) andlitigants (e.g., Boyd 2015;Caldeira and Wright 1988), the prestige of particular state court systems, as well as the various political, social, and economic circumstances responsible for the events that generated the original complaint (Boyd 2017;Brunn et al 2000).…”
Section: Geographic Variation and The Legal Systemmentioning
confidence: 99%
“…In closely competitive states, minority parties in particular seek to use the judicial system to advance their position in myriad ways. Courts become an avenue for making claims that would not receive a favorable or timely reception by other institutions of state government (Dumas 2016, 296; Yates, Tankersley, and Brace 2010). A reasonable hypothesis follows—a larger number of redistricting cases will originate in states and at times when there is hard-fought competition between the parties for control of government.…”
Section: Political Motivations Behind Redistricting Litigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Different jury verdict reporters vary in their comprehensiveness and level of detail. Most jury verdict reporters function at the state level and so their quality also varies by state . Moreover, Westlaw contains data from only some jury verdict reporters.…”
mentioning
confidence: 99%
“…As a result of Westlaw’s system for collecting information on medical malpractice cases, data on malpractice cases from states with more comprehensive jury verdict reporters are overrepresented, as are large awards, which are more likely to be picked up by the jury verdict reporters . Given that the malpractice case samples obtained from Westlaw are both incomplete and unrepresentative, it is difficult to draw meaningful conclusions from case percentages based on these Westlaw data, as Thiels et al report in their article and eTable.…”
mentioning
confidence: 99%